Keratin-based Materials - Reddy, Narendra (De Gruyter, 2020)
The book introduces readers to the unique aspects of keratin and opportunities to develop various bioproducts and biomaterials from keratins. It discusses the structure, properties and specific applications of keratins extracted from different sources. Applications include keratins as absorbents, reinforcements or matrices for composites, hydrogels and fibres.